Вплив концентрації бактерій на протимікробну активність декаметоксину = Influence of concentration on bacteria the activity the antimicrobial activity decamethoxinum - Stukan, Oksana K. (Journal of Education, Health and Sport, 2015)
Stukan Oksana. Вплив концентрації бактерій на протимікробну активність декаметоксину = Influence of concentration on bacteria the activity the antimicrobial activity decamethoxinum. Journal of Education, Health and Sport. 2015;5(6):291-296. ISSN 2391-8306. DOI 10.5281/zenodo.18614 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A291-296 https://pbn.nauka.gov.pl/works/566838 http://dx.doi.org/10.5281/zenodo.18614 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 14.06.2015. УДК; 615.27 ВПЛИВ КОНЦЕНТРАЦІЇ БАКТЕРІЙ НА ПРОТИМІКРОБНУ АКТИВНІСТЬ ДЕКАМЕТОКСИНУ Influence of concentration on bacteria the activity the antimicrobial activity decamethoxinum О. К. Стукан Oksana Stukan ВНМУ ім.М.І.Пирогова, кафедра мікробіології, вірусології та імунології, Вінниця Vinnitsky National Medical University named M.I.Pirogova, department of Microbiology Abstract The use domestic antiseptic preparations in medicine allowed considerably improve the efficiency prophylaxis and treatment of of many diseases infectious genesis. It is known that they are active in in the presence of the products tissue decay; operate in acidic and alkaline environments do not cause local irritating. Preparations fixed form based decamethoxinum have inhibitory and the bactericidal action on bacteria, viruses, fungi and detoxic effect on staphylococcal, diphtheritic exotoxin, possess good regenerative effect against allergies. The study was conducted at clinical strains of Staphylococcus aureus by standard serial dilutions. The results showed high activity and effectiveness of the drug decamethoxinum. The use of domestic of antiseptics preparations in medicine allowed considerably improved the effectiveness prophylaxis and treatment of many diseases of infectious genesis. It is known that they are active in the presence of the products tissue decay; operate in acidic and an alkaline environments do not cause local irritating. Investigation of antimicrobial activity decamethoxinum (DCM), carried out in clinical strains of Staphylococcus aureus. From different medical patients, prophylactic establishments, we have removed and been identified 187 clinical strains of microorganisms. Results of the study of antimicrobial activity decamethoxinum on clinical strains of Staphylococcus aureus have shown the following. The minimum bacteriostatic the concentration of DCM was equal to 0,75 ± 0,06 mg / ml, the minimum bactericidal concentration DCM has increased to 1,5 ± 0,06 mg / ml. The dependence of the biological activity of antimicrobial compounds on the number of microorganisms due to a decrease the number of available of molecules existing centers the active compound of by microorganisms in the conditions of the saturated substrate. In the process of studying of sowing dose test microorganisms to antimicrobial activity of antiseptics preparations the following results. To explore dependence of actions on the magnitude of the microbial load in a clinical setting, we studied the effect DCM clinical strains are Staphylococcus aureus. MIC DCM for clinical strains of microbial load 10³ CFU / ml was equal 4,56 ± 0,93mkh / ml, while the load 106 CFU / mL DCM MIC was equal to 4,69 ± 1,6 mg / ml. MCC DCM microbial load of 109 cfu / ml was 9,57 ± 3,96 mg / ml. Conclusion. Investigational antiseptic dasg decamethoxin has a wide range of antimicrobial activity on causative agents of nosocomial infections, retains a high antimicrobial activity, quickly detoxifies microorganisms. Our results demonstrated strong the activity of DCM clinical strains are Staphylococcus. Key words: staphylococcus, clinical strains, CFU, decamethoxinum, antimicrobial activity, concentration Резюме Влияние концентрации бактерий на противомикробную активность декаметоксина. Использование отечественных антисептических препартов в медицине позволило значительно улучшить эфективность профилактики и лечения госпитальных заболеваний инфекционного генеза. Известно, что они проявляют активность в присутствии продуктов тканевого разпада; действуют в кислой и щелочной среде, не вызывают местного раздражающего эффекта. Лекарственные формы на основе декаметоксина владеют бактериостатическим и микробоцидным действием на бактерии, вирусы, грибы, а также имеют иннактивирующее действие на стафилококовый, дифтерийный экзотоксины, имеют отличное регенераторное и противоалергическое действие. Исследование проведено на клинических штаммах стафилококка методом стандартных серийных разведений. Результаты исследований показали высокую активность и эффективность препарата декаметоксина. Ключевые слова: стафилококк, клинические штаммы, КОЕ декаметоксин, антимикробная активность, концентрация. Резюме Застосування вітчизняного антисептичного препаратів в медицині дозволило значно покращити ефективність профилактики та лікування госпітальних хвороб інфекційного генезу. Відомо, що вони проявляють активність в присутності продуктів тканинного розпаду; діють в кислому та лужному середовищах, не викликають місцеву подразнювальну дію. Лікарські фіксовані форми на основі декаметоксину володіють бактеріостатичною та мікробоцидною дією щодо бактерій, вірусів, грибів, а також детоксикуючою дією щодо стафілококового, дифтерійного екзотоксинів, мають гарну регенеративну та протиалергійну дію. Дослідження проведено на клінічних штамах стафілокока методом стандартних серійних розведень. Результати досліджень показали високу активність та ефективність препарату декаметоксину. Ключові слова: стафілокок, клінічні штами, КУО, декаметоксин, антимікробна активність, концентрація.